2015
DOI: 10.3390/molecules20069510
|View full text |Cite
|
Sign up to set email alerts
|

Combine Use of Selected Schizosaccharomyces pombe and Lachancea thermotolerans Yeast Strains as an Alternative to theTraditional Malolactic Fermentation in Red Wine Production

Abstract: Most red wines commercialized in the market use the malolactic fermentation process in order to ensure stability from a microbiological point of view. In this second fermentation, malic acid is converted into L-lactic acid under controlled setups. However this process is not free from possible collateral effects that on some occasions produce off-flavors, wine quality loss and human health problems. In warm viticulture regions such as the south of Spain, the risk of suffering a deviation during the malolactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(187 citation statements)
references
References 48 publications
13
173
1
Order By: Relevance
“…However, there were no significant differences in ethanol concentrations in wines made with S. cerevisiae only and a combination of Sc + LAB1. This is in agreement with work by Benito et al (2015), who also reported no significant differences in ethanol concentrations in wines made with S. cerevisiae only and wines made with a combination of S. cerevisiae + O. oeni. Lactic acid bacteria, S. cerevisiae, H. uvarum and M. pulcherrima in combination positively affected the phenolic acid concentrations of the wines ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…However, there were no significant differences in ethanol concentrations in wines made with S. cerevisiae only and a combination of Sc + LAB1. This is in agreement with work by Benito et al (2015), who also reported no significant differences in ethanol concentrations in wines made with S. cerevisiae only and wines made with a combination of S. cerevisiae + O. oeni. Lactic acid bacteria, S. cerevisiae, H. uvarum and M. pulcherrima in combination positively affected the phenolic acid concentrations of the wines ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…BAs were mostly formed during spontaneous alcoholic fermentation. In fact, total BAs concentrations raised ranging from 1.65 (Greco Nero) to 2.9 (Arvino) and accounting for no less than 79% of the final BAs amounts in wines [63]. This indicates that in the considered samples, the presence of BAs was linked to AF more than to MLF, as already reported by Wang et al [53].…”
Section: Bas and Alcoholic Fermentationsupporting
confidence: 76%
“…This is the reason that certain non-Saccharomyces yeast, such as Schizosaccharomyces, which have the ability to lower the malic acid content of wine, could prove to be an excellent alternative to lactic acid bacteria and are currently viewed with much interest (Benito et al, 2015b(Benito et al, , 2014aFleet, 1999;Suárez-Lepe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%